2009
DOI: 10.1007/s00216-009-2987-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of steroidal saponins in saponin extract from Paris polyphylla by liquid chromatography tandem multi-stage mass spectrometry

Abstract: Rhizoma Paridis saponins are bioactive steroidal saponins derived from Paris polyphylla. Optimization of the ionization process was performed with electrospray ionization tandem mass spectrometry in both positive and negative-ion modes. Negative-ion ESI was adopted for generation of the precursor deprotonated molecules to achieve the best ionization sensitivity for the analytes. Positive ionization was used to choose the most abundant fragment ion. Furthermore, according to the characteristic fragmentation beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 12 publications
4
42
1
Order By: Relevance
“…In the MS, the steroid saponins exhibited quasi-molecular ions [M+H] + , [M−H] − , or whilst in the MS n spectra fragment ions were formed by successive or simultaneous loss of saccharide groups, H 2 O or CH 3 OH. The detailed fragmentation pathways have been discussed before [25].…”
Section: Identification and Distribution Of Other Saponins By Esi-ms mentioning
confidence: 99%
See 1 more Smart Citation
“…In the MS, the steroid saponins exhibited quasi-molecular ions [M+H] + , [M−H] − , or whilst in the MS n spectra fragment ions were formed by successive or simultaneous loss of saccharide groups, H 2 O or CH 3 OH. The detailed fragmentation pathways have been discussed before [25].…”
Section: Identification and Distribution Of Other Saponins By Esi-ms mentioning
confidence: 99%
“…Highest sensitivity, relatively short analysis time, considerable structural information, low amount of sample and on line identification of separated saponins should be recommended as their competitive advantages. In our previous research, we identified 23 steroid saponins from P. yunnanensis and deduced their fragmentation pathways [25]. In the present paper, we used LC-MS/MS to identify the common steroid saponins and compared their ingredient variability in Paris and Trillium plants.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the above potential biological effects, it is necessary to carry out the bioanalysis and pharmacokinetic studies on Polyphyllin D and Paris H. The in vitro quantitative methods of Polyphyllin D and Paris H analysis have been carried out in the last several years mainly by liquid chromatography with both reversed phase columns coupled to diode array detector (DAD) and evaporative light scattering detector (ELSD) [17][18][19][20]. None of these methods meets the requirements for the analysis of biological fluids with respect to an efficient clean-up procedure, shorter running time and higher sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…The analytical process was completed in 60 min. According to the profile of dried rhizomes of the PPY extract, the main ingredients found were Paris VII, Paris H, formosanin C, gracillin and polyphyllin D (Kang et al, 2012;Liu et al, 2013;Man et al, 2009a). Therefore, those five saponins were used as the quantitative criteria in the study of this separation process.…”
Section: Hplc-uv Analysismentioning
confidence: 99%
“…It appeared with the name ''ZaoXiu'', and many wellknown formulary Chinese Medicines contain Rhizoma Paridis, such as Yunnan Baiyao Powder and Gongxuening Capsules produced by Yunnan Baiyao Group Ltd. Co. (Yunnan, China), Loulian Capsules (Tonghua Wantong Pharmaceutical Ltd. Co., Tonghua, China), Jidesheng Sheyao Tablet (Nantong Jinghua Pharmaceutical Ltd. Co., Nantong, China). Rhizoma Paridis saponins (RPS) (Man et al, 2009a), as steroidal saponins, are the main and the active components in PPY (Liu et al, 2012;Qin et al, 2012;Zhang et al, 2010). They recently attracted particular interests because modern pharmacology research indicated these steroidal saponins appeared to exhibit a variety of biological activities, such as antitumor (Man et al, 2009b(Man et al, , 2011a, antifungal activity (Deng et al, 2008), inhibitory activities against abnormal uterine bleeding (Fu et al, 2008) and anthelmintic activity (Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%